Centering community voices: advancing health equity for people and pets in Los Angeles County through community-based participatory research - Morales, Celeste; Ruelas, Miguel; Daluz, Terryl; Analco, Elizabeth; Vera, Nicole; Rivera, Janet; Covington, Megan; Hawes, Sloane M. (Frontiers in Veterinary Science, 2025)
BackgroundPets are increasingly seen as members of the family unit in U.S. households. To advance health equity and improve health service providers’ understanding of how to best support pet owners, this study aimed to understand the priorities and barriers to human and companion animal (pet) well-being services and resources in Los Angeles County, CA, USA.MethodsA community-based participatory research (CBPR) approach was used to conduct five semi-structured focus groups in May 2024 with 27 pet owners in Los Angeles County, CA, USA. Data were analyzed using an inductive approach.ResultsSeveral themes for improving health services for people and pets were identified, including: understanding community-specific priorities for people and pets in Los Angeles County; addressing barriers to services and information for people and pets; addressing the need for affordable pet inclusive housing and tenants rights; and addressing the need for improved access to pet inclusive green spaces and environmental justice. The participants shared about the importance of mutual aid and collective care when faced with a lack of access to services.DiscussionThese findings can be used across health services to inform the development of equitable, accessible, and community-specific solutions that improve the quality of life for both people and their pets in Los Angeles County, CA, USA.